A Comparison of Ligase Chain Reaction to Polymerase Chain Reaction in the Detection of Chlamydia trachomatis Endocervical Infections - J. D. Davis; P. K. Riley; C. W. Peters; K. H. Rand (Hindawi Limited, 1998)
Objective: To compare the reliability of ligase chain reaction (LCR) to polymerase chain reaction (PCR) in detecting Chlamydia trachomatis endocervical infections.